Patients Satisfaction with Dental Service, School of Dentistry, University of Costa Rica = Satisfacción de los usuarios del Servicio de Odontología, Universidad de Costa Rica - Gutiérrez Marín, Natalia 1975-; López Soto, Andrea María 1987- (2023)
The objective of this research was to use the Dental Satisfaction Questionnaire to determine the level of patient's satisfaction who come to the School of Dentistry of the University of Costa Rica. The research was conducted with the entire population of patients who received dental care in the Undergraduate Student Clinics of the School of Dentistry between April and September 2021. A digital survey was generated with the questions of the DSQ and sociodemographic variables, which was sent by email. Descriptive statistics were performed to establish the absolute and relative frequency, as well as measures of central tendency and variability, according to the nature of the variables. The Kolmogorov-Smirnov test was used in the conformity assessment of the data for the normal distribution. The relationships between the scores obtained from the Dental Satisfaction Questionnaire and the sociodemographic variables were analyzed using the Mann-Whitney U Test and the Kruskal-Wallis Test. A response rate of 36% was obtained. 98.5% of the subjects were satisfied with the services received. There was a statistically significant difference between the frequency of visits and the dental satisfaction scale (p=0.001). The scoring by type of clinic with regards to access, pain management, cost and availability were statistically significant (p=0.001, p=0.014, p=0.001, p=0.001, respectively). The differences in the relationship between the age groups and access was significant (p=0.014); in addition to that between education level and cost (p=0.001). A large majority of patients who come to the services of the School of Dentistry UCR are satisfied with the service received.
El objetivo de esta investigación fue utilizar el cuestionario DSQ para determinar el nivel de satisfacción de los pacientes que acuden a la Facultad de Odontología de la UCR. La investigación se realizó con toda la población de pacientes que recibieron atención dental en las Clínicas de pregrado y grado de la Facultad de Odontología UCR entre abril y setiembre del 2021. Se generó una encuesta digital con las preguntas del cuestionario DSQ y variables sociodemográficas, la cual se envió por medio del correo electrónico. Se realizó estadística descriptiva estableciendo la frecuencia absoluta y relativa, así como medidas de tendencia central y variabilidad, según la naturaleza de las variables. La prueba de Kolmogorov-Smirnov fue utilizada en la evaluación de la conformidad de los datos para la distribución normal. Las relaciones entre las puntuaciones obtenidas del Cuestionario de Satisfacción Dental y las variables sociodemográficas se analizaron mediante las pruebas de Prueba U de Mann-Whitney y la Prueba de Kruskal-Wallis. Se obtuvo un índice de respuesta del 36%. El 98,5% de los sujetos estuvo satisfecho con los servicios recibidos. Hubo diferencia estadísticamente significativa entre la frecuencia de visitas y la escala de satisfacción dental (p=0,001). También hubo diferencia estadísticamente significativa entre las diferentes clínicas y el acceso, manejo del dolor, costo y disponibilidad (p=0,001, p=0,014, p=0,001, p=0,001, respectivamente). De igual forma, hubo diferencia significativa en los grupos de edad y el acceso (p=0,014) y entre el nivel educativo y el costo (p=0,001). Una gran mayoría de los pacientes que acuden a los servicios de la Facultad de Odontología UCR están satisfechos con el servicio recibido.
En revista Odóvtos, vol. 25, no.1 (enero-abril 2023)
Descripción basada en el contenido visto el 13 de diciembre, 2024
También disponible en formato HTML y EPUB